2004
DOI: 10.1111/j.1475-6765.2004.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

How multilevel structures affect environmental policy in industrialized countries

Abstract: Abstract.  Extensive decentralization and devolution efforts among industrialized nations throughout the 1980s and 1990s call for a closer look at the effect these trends have on public policy. This article investigates the impact of these trends on the environmental performance of industrialized countries. There are two competing hypotheses as to how federalism and other multilevel governance structures affect the environmental performance of countries. The first stresses that the resulting institutional frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 42 publications
(64 reference statements)
2
23
1
7
Order By: Relevance
“…This result is in line with Wälti [53], who points out that party politics seem to have no impact on environmental performance. Other authors, such as Midlarsky [31], have found a negative relation between democracy and three environmental indicators, deforestation, carbon dioxide emission and soil erosion by water, contrary to prediction.…”
Section: Discussion Of Resultssupporting
confidence: 80%
“…This result is in line with Wälti [53], who points out that party politics seem to have no impact on environmental performance. Other authors, such as Midlarsky [31], have found a negative relation between democracy and three environmental indicators, deforestation, carbon dioxide emission and soil erosion by water, contrary to prediction.…”
Section: Discussion Of Resultssupporting
confidence: 80%
“…These findings confirm a growing literature claiming a positive link between federal systems and environmental effectiveness (see Wa¨lti 2004 for a review of this). It should be noted, however, that these findings stand in stark contrast to Campbell and Thomas's (2002) claim that federalism inhibited biodiversity conservation in Canada; however, the Canadian study focuses on just this one case.…”
Section: Resultssupporting
confidence: 80%
“…Federal systems also display more sensitivity to subnational concerns and provide more access points to government (Kincaid 2001). For example, Weidener (1995) and Czada (1993) found in Germany, and Knoepfel (1997) found in Switzerland, that federalism promoted nuclear power safety primarily because promoters of the environmental interest have been able to make use of the multiple access points in the German and Swiss federal systems (Wa¨lti 2004). Therefore we can expect that federal governmental structures will be positively related to environmental effectiveness.…”
Section: Clarifying the Debatementioning
confidence: 99%
“…None of these papers incorporate multiple government political units or federalism into the analysis, however. 2Wälti (2004) reports that multilevel government structures affect pollution levels in the OECD, but ignores corruption Fredriksson and Millimet (2007). study the effect of bicameralism on the dispersion of environmental policy outcomes in the presence of corruption Treisman (2000).…”
mentioning
confidence: 99%